Assessment of Fear of Failure Among Medical Students at King Saud University - Alabduljabbar, Abeer; Almana, Lyan; Almansour, Alanoud; Alshunaifi, Aljoharah; Alobaid, Nada; Alothaim, Norah; Shaik, Shaffi Ahamed (Frontiers in Psychology, 2022)
Background Fear of failure (FoF) is described as a “dispositional tendency to avoid failure in achievement settings.” It may potentially and adversely affect students’ ability to perform well in their educational activities. Objectives To measure FoF among medical students at King Saud University, FoF between men and women, academic levels, grade point average (GPA), and other factors among medical students were compared. Method A cross-sectional observational study was carried out using a stratified random sampling method. A total of 455 medical students completed “the Performance Failure Appraisal Inventory” during the academic year 2019–2020 at King Saud University, Riyadh, Saudi Arabia. Results The results showed that the mean of FoF was −0.3117. Moreover, higher levels of fear of devaluing one’s self-estimate were seen in women, and higher levels of fear of important others losing interest were seen in men. A significant relation was seen between different academic levels and fear of shame and embarrassment, fear of upsetting important others, as well as FoF. Higher levels of FoF were seen in those who had a GPA below 3.5 and a GPA greater than 4.9. Also, it was high in students who were not interested in studying medicine. The Cronbach’s α value of 0.93 of all items indicates good internal consistency, and the factor analysis confirms five items of an instrument. Conclusion The overall level of FoF was low among medical students at King Saud University. However, the domains and levels of FoF differed significantly according to gender, academic level, GPA, and interest in studying medicine.